Formulasi Dan Evaluasi Granul Effervescent Kombinasi Ekstrak Kering Rimpang Jahe Merah, Temulawak Dan Kayu Manis - Wahyu Margi Sidoretno (LPPM Universitas Abdurrab, 2022)
Effervescent granules are coarse to very coarse powders containing medicinal elements in a dry mixture. It’s consist of sodium bicarbonate, citric acid, and tartaric acid when added to water, the acid and base react to liberate carbon dioxide to produce foam. Effervescent can produce a pleasant taste due to the presence of carbonates which can help improve the taste of certain drugs. This objective of this study is to determine mixture of dry red ginger rhizome extract, curcuma and cinnamon’s effervescent granules and meets the criteria for good effervescent granules. The method on this study used wet granulation with four formula variations, namely F1: ordinary granules, F2: effervescent granules without active substances, F3 and F4 were effervescent granules with variations in acid and base. Evaluation of the physical quality of granules includes water content test, compressibility test, flow time test, angle of repose, liquid absorption test, Scanning Electron Microscope (SEM), dispersion time and pH. Based on the experimental results, the combination of dry red ginger rhizome extract, curcuma and cinnamon can be formulated into effervescent granules. The preparation of effervescent granules combined with dry extract of red ginger rhizome, curcuma and cinnamon did not meet the criteria for a good effervescent granule, namely the water content test of the granules F2, F3, F4 each obtained 6.47±0.07, 6.61±0.03, and 5.82±0.04% where the range of good granule moisture content is 2-5%.